THE SPECIFICITY OF LEGAL SUBJECTS IN POLISH AND ITALIAN ENVIRONMENTAL PROTECTION LAW - Rakoczy, Bartosz (Review of European and Comparative Law, 2019)
It should be noted that both the Polish lawmaker and Italian lawmaker are aware of the specificity of legal subjects in the public domain. They can see that public administration bodies and public institutions cannot be described in normative terms, definitions and expressions used in legal language. New criteria for their separate treatment are needed. In addition, it is justified to treat them separately from all public administration bodies and public subjects. This only serves as proof of the rank and significance of such authorities.